Analisis efisiensi penerapan teknologi akuaponik (studi kasus usaha budidaya ikan nila pada kolam Fakultas Perikanan dan Ilmu Kelautan Universitas Halu Oleo - Ansa, Ardin; Nadia, La Ode Abdul Rajab; Piliana, Wa Ode; A, Nurdiana; Riani, Irdam (Jurnal Sosial Ekonomi Perikanan, 2022)
The study was conducted at the Faculty of Fisheries and Marine Sciences at Halu Oleo University in June 2019 to February 2020. The first cycle occurred in July-October 2019, the second cycle occurred in November 2019-February 2020. The research objective was to determine the cost efficiency of Fish farming Organic tilapia based on aquaponics technology. This research uses a case study method with 1 respondent. Data obtained through interviews using questionnaires, observation, documentation, and literature studies. Data collected includes the total costs incurred, the amount of production in two cycles, the selling price. Data were analyzed descriptively quantitatively. Cost analysis is calculated by the formula TC = (TFC + TVC), efficiency analysis is calculated by the formula (E) = TC / Q, Revenue is calculated by the formula TR = P.Q while the Profit is calculated by the formula π = TR - TC. The total cost incurred in the first cycle in aquaponic cultivation is Rp.25,342,789 / cycle while the total cost in the second cycle is Rp23,107,789 / cycle. The total revenue of the first cycle of aquaponics cultivation is Rp.39,590,000 / cycle while in the second cycle it is Rp.47,310,000 / cycle. The profit of aquaponic cultivators in the first cycle is IDR 14,247,211 / cycle, while the profit in the second cycle is IDR 24,202,211 / cycle. Based on the analysis of cost efficiency in the first cycle obtained Rp24,943 / Kg, while the results of the efficiency analysis in the second cycle amounted to Rp18,650 / Kg, so that the cost efficiency of aquaculture technology-based tilapia aquaculture in the Pool of the Faculty of Fisheries and Marine Sciences at Halu Oleo University in Kendari is contained in the second cycle which is Rp. 18,650 / kg.